THE SPECIFIC CHARACTERISTICS OF FREE TRADE ZONE INTERNATIONAL AGREEMENTS CONCLUSION BETWEEN MEMBER STATES OF INTEGRATION ASSOCIATIONS AND THIRD COUNTRIES - Sagidan Анар Жарылкасыновна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2023)
In this article author considering the specific characteristics of free trade zone international agreements conclusion between Member States of integration associations and third countries.